The impact of level of neonatal care provision on outcomes for preterm babies born between 27 and 31 weeks of gestation, or with a birth weight between 1000 and 1500 g: a review of the literature - Ismail, AQT; Boyle, EM; Pillay, T; OptiPrem Study Group (BMJ, 2020)
Objective There is evidence that birth and care in a maternity service associated with a neonatal intensive care unit (NICU) is associated with improved survival in preterm babies born at <27 weeks of gestation. We conducted a systematic review to address whether similar gains manifested in babies born between 27+0 and 31+6 weeks (hereafter 27 and 31 weeks) of gestation, or in those with a birth weight between 1000 and 1500 g.